Advances in CAR T cell immunotherapy for paediatric brain tumours - Rao, Padmashree; Furst, Liam; Meyran, Deborah; Mayoh, Chelsea; Neeson, Paul J.; Terry, Rachael; Khuong-Quang, Dong-Anh; Mantamadiotis, Theo; Ekert, Paul G. (Frontiers in Oncology, 2022)
Brain tumours are the most common solid tumour in children and the leading cause of cancer related death in children. Current treatments include surgery, chemotherapy and radiotherapy. The needs for aggressive treatment means many survivors are left with permanent severe disability, physical, intellectual and social. Recent progress in immunotherapy, including genetically engineered T cells with chimeric antigen receptors (CARs) for treating cancer, may provide new avenues to improved outcomes for these patients with paediatric brain cancer. In this review we discuss advances in CAR T cell immunotherapy, the major CAR T cell targets that are in clinical and pre-clinical development with a focus on paediatric brain tumours, the paediatric brain tumour microenvironment and strategies used to improve CAR T cell therapy for paediatric tumours.